Hydride-induced Meisenheimer complex formation reflects activity of nitro aromatic anti-tuberculosis compounds. Issue 1 (4th January 2021) - Liu, Rui; Markley, Lowell; Miller, Patricia A.; Franzblau, Scott; Shetye, Gauri; Ma, Rui; Savková, Karin; Mikušová, Katarína; Lee, Bei Shi; Pethe, Kevin; Moraski, Garrett C.; Miller, Marvin J.
Abstract : The formation efficiency of hydride-induced Meisenheimer complexes of nitroaromatic compounds is consistent with their anti-TB activities exemplied by MDL860 and benzothiazol N -oxide (BTO) analogs. Abstract : The formation efficiency of hydride-induced Meisenheimer complexes of nitroaromatic compounds is consistent with their anti-TB activities exemplied by MDL860 and benzothiazol N -oxide (BTO) analogs. Herein we report that nitro cyano phenoxybenzenes (MDL860 and analogs) reacted slowly and incompletely which reflected their moderate anti-TB activity, in contrast to the instantaneous reaction of BTO derivatives to quantitatively generate Meisenheimer complexes which corresponded to their enhanced anti-TB activity. These results were corroborated by mycobacterial and radiolabelling studies that confirmed inhibition of the DprE1 enzyme by BTO derivatives but not MDL860 analogs.